The validation of a swimming turn wall-contact-time measurement system - Brackley, V.; Ball, K.; Tor, E. (ISBS Proceedings Archive (Michigan), 2017)
The effectiveness of the swimming turn is highly influential to overall performance in competitive swimming. The push-off or wall contact, within the turn phase, is directly involved in determining the speed the swimmer leaves the wall. Therefore, it is paramount to develop reliable methods to measure the wall-contact-time during the turn phase for training and research purposes. The aim of this study was to determine the reliability and concurrent validity of the Pool Pad system to measure wall-contact-time during the turn. Despite measurement differences, the results analyses demonstrated that the Pool Pad is suitable for measuring wall-contact-time within a training environment.